2006
DOI: 10.1007/s00402-006-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of an acute compartment syndrome of the thigh

Abstract: Compartment syndromes of the thigh after blunt trauma without any fracture are rare. Most surgeons recommend operative treatment. There are different rules for compartment syndromes of the thigh in young athletes after blunt trauma compared to compartment syndromes at other locations [(1) the large volume of the quadriceps muscle, (2) its relatively elastic fascia, (3) the direct proximal contact to the hip muscles which allows extravasation of fluid out of the compartment)]. We present a case of conservative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…This may be because the thigh compartments are large and encapsulated with dilative fascia,6 and therefore can readily accommodate expansion. Thigh compartments also blend anatomically with the hip,7 which can provide additional space into which the accumulating fluid may be discharged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the thigh compartments are large and encapsulated with dilative fascia,6 and therefore can readily accommodate expansion. Thigh compartments also blend anatomically with the hip,7 which can provide additional space into which the accumulating fluid may be discharged.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic ACS of the thigh in sport has been reported in football,6 41 44 handball,41 44 American football,38 46 lacrosse,39 softball,54 karate,56 kickboxing43 and in one case of a rugby player 41…”
Section: Introductionmentioning
confidence: 99%
“…There is one case report 13 in the literature of a high-class athlete returning to sport after fasciotomy of the thigh but in general this is unlikely owing to residual muscular deficits. Reide et al 20 presented a case of conservatively managed blunt trauma to the thigh where, despite an elevated intracompartmental pressure fasciotomy was delayed and resolution occurred. As in this case, they found that a return to activity was possible but with a long healing time.…”
Section: Discussionmentioning
confidence: 98%
“…A conservative approach is only advisable if no fracture, penetrating trauma or neurovascular deficit exist. 20 A return to activity is achievable using this approach.…”
Section: Discussionmentioning
confidence: 98%
“…Measuring intracompartmental pressures provides a quantitative threshold for performing fasciotomies when the clinical scenario is obscure, but a clinical decision by the physician can be made as well. A difference between the diastolic pressure and the measured intracompartmental pressure <30 mm Hg (δ pressure) or absolute intracompartmental pressure of 30 or 45 mm Hg serves as an indication for surgical intervention and fasciotomy 35 52 53. CST is associated with an increased time to the operating room (4.3–19.8 hours) due to lack of recognition and rare presentation, resulting in suboptimal outcomes 54–56.…”
Section: Discussionmentioning
confidence: 99%